1993
DOI: 10.1021/ja00079a032
|View full text |Cite
|
Sign up to set email alerts
|

Hexanuclear ferric complexes possessing different degrees of spin frustration

Abstract: The synthesis, single-crystal X-ray structures, and magnetochemical properties are reported for two new hexanuclear ferric complexes, [Fe6(M3-0)2(M2-OH)2(M2-02CCH3)io(C7HnN20)2]4CH2Cl2 (9-4CH2Cl2) and [Fee0*3-0)2(C6H6N0)8C14](C104)24MeCN (KMMeCN). The ligand C7HnN20-is the anion of 2-(7V-methylimidazol-2yl)-2-hydroxypropane and C6H6NO™ is the anion of 2-pyrididylcarbinol. The reaction of [Fe3G(OAc)6(py)3] C104 in acetonitrile with 2-(iV-methylimidazol-2-yl)-2-hydroxypropane gives a brown oil which can be cryst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
39
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 0 publications
5
39
0
Order By: Relevance
“…It was also assumed that J 12 = J 13 due to approximate symmetry. Values obtained from the fit were J 12 = J 13 = −18 cm −1 , J 23 = −52 cm −1 , and J 24 = −3 cm −1 84, indicating that the ground state has S = 0. However, a variable‐field magnetization experiment indicated that the spin of the ground state is three.…”
Section: Test Casesmentioning
confidence: 98%
See 1 more Smart Citation
“…It was also assumed that J 12 = J 13 due to approximate symmetry. Values obtained from the fit were J 12 = J 13 = −18 cm −1 , J 23 = −52 cm −1 , and J 24 = −3 cm −1 84, indicating that the ground state has S = 0. However, a variable‐field magnetization experiment indicated that the spin of the ground state is three.…”
Section: Test Casesmentioning
confidence: 98%
“…The base of the triangle is bridged only by the central oxide ligand, and has an iron–iron distance of 3.67 Å. The structure is somewhat unusual, as most triangular iron carboxylate complexes are equilateral 84. Exchange constants (Fig.…”
Section: Test Casesmentioning
confidence: 99%
“…Another very well investigated class of molecules is given by spin rings among which iron rings ("ferric wheels") are most popular [27,28,29,30,31,32,33,34]. Iron-6 rings for instance can host alkali ions such as lithium or sodium which allows to modify the parameters of the spin Hamiltonian within some range [16,35].…”
Section: Fig 2: Structure Of a Chromium-4 And A Chromium-8 Ring Thementioning
confidence: 99%
“…1) in an attempt to introduce molecules that can compete with the phenolic oximes for the metal coordination sites and in the hope that novel coordination cages would form. The co-ligands were chosen based on their previous success in synthesising Fe III clusters, as reported in the literature [30][31][32][33][34][35][36][37][38][39]. For example, the ligand tacn was used in the synthesis of the first recognised Fe III Single-Molecule Magnet (SMM), [Fe 8 ] [40,41], and hmpH and pdmH 2 have both been used extensively in metal cluster synthesis [30-32, 35, 36, 42-51].…”
Section: Introductionmentioning
confidence: 99%